Cytokine secretion profiles of cloned T cells from human aortic atherosclerotic plaques - de Boer, Onno J.; van der Wal, Allard C.; Verhagen, Claudia E.; Becker, Anton E. (The Journal of pathology, 1999)
T cells take part in the chronic inflammatory reaction in atherosclerotic plaques, but their specific role in atherosclerosis has not yet been fully elucidated. Nevertheless, one may anticipate that activated T cells may secrete cytokines capable of modulating the morphology and hence the stability of plaques by regulating cell proliferation, lipid metabolism, and extracellular matrix (ECM) synthesis and/or degradation. This study has been designed to investigate the functional properties of T cells in atherosclerotic lesions. For this purpose, T‐cell clones were generated from atherosclerotic plaques isolated from human aortas obtained at autopsy from six subjects. Cloned cells were activated with PMA and OKT‐3 to initiate cytokine production and cytokine profiles of CD4‐positive clones were measured by ELISA. The majority of the T‐cell clones (125/155, 81 per cent) produced both interferon (IFN)‐γ and interleukin (IL)‐4 (type 0 cytokine profile). Moreover, the production of IFN‐γ was dominant in the majority of these clones. A type 1 cytokine profile (high levels of IFN‐γ and low levels of IL‐4) was found in 17 per cent of the clones (27/155). Only three clones (2 per cent) showed a type 2 cytokine secretion pattern (high levels of IL‐4 and low levels of IFN‐γ). No cytolytic activity could be established in plaque‐derived T cells. Our results show that the T‐cell population in atherosclerotic lesions is heterogeneous, but the most dominant T cell by far is the one with a type 0 cytokine profile. The dominant secretion of IFN‐γ by T‐cell clones suggest an important role for plaque T cells in modulating the growth and differentiation of other cells, such as macrophages and smooth muscle cells in atherosclerotic plaques. Copyright © 1999 John Wiley & Sons, Ltd.